2020
DOI: 10.1038/s41598-020-79195-0
|View full text |Cite
|
Sign up to set email alerts
|

Somatic alterations and mutational burden are potential predictive factors for metachronous development of early gastric cancer

Abstract: The risk of developing metachronous gastric cancer (MGC) following curative endoscopic submucosal dissection (ESD) of early gastric cancer (EGC) remains even after eradicating Helicobacter pylori (HP) successfully. We screened initial EGC and adjacent non-cancerous mucosa ESD-resected specimens for somatic variants of 409 cancer-related genes, assessing their mutational burden (MB) to predict molecular markers for metachronous post-ESD development. We compared variants between ten patients diagnosed with MGC m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Finally, gastric neutrophilic infiltration in the corpus [23], methylation level of miR-124a-3 gene [24], and somatic genomic alterations (RECQL4, JAK3 m, ARID1A, and MAGl1 genes) [25] were associated with MGC development in single studies.…”
Section: Endoscopic and Histological Factorsmentioning
confidence: 96%
See 1 more Smart Citation
“…Finally, gastric neutrophilic infiltration in the corpus [23], methylation level of miR-124a-3 gene [24], and somatic genomic alterations (RECQL4, JAK3 m, ARID1A, and MAGl1 genes) [25] were associated with MGC development in single studies.…”
Section: Endoscopic and Histological Factorsmentioning
confidence: 96%
“…According to the aforementioned search strategy and after removal of duplicates, a total of 889 studies were identified. After excluding irrelevant citations, 208 papers were assessed for full-text screening, of which 52 met inclusion/exclusion criteria and were included in the systematic review [6,7,9,10,12,13,[17][18][19][20][21][22][23][24][25][26]; plus references 1s-36 s in the online-only Supplementary material (▶ Fig. 1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…These results may be reasonable, as several studies have shown that MSI and/or hMLH1 methylation is not useful for prediction of the development of GC [ 9 , 40 ]. On the other hand, genetic researchers have continuously investigated and identified some candidate molecular markers (methylation of microRNA-34b/c and -124a3 or somatic mutation of ARID1A and MAGI1 ) for prediction of the development of metachronous GC [ 41 , 42 , 43 ]. However, since molecular alterations in GC patients are very complex and diverse [ 37 , 38 , 39 ], it might be difficult to select a specific genetic marker that can predict the development of synchronous/metachronous GCs.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding MAGI1, a recent report revealed that MAGI1 mediates tumor metastasis through the c-Myb/miR-520h/MAGI1 signaling pathway in renal cell carcinoma [125]. Somatic genomic alterations of MAGI1 genes were also found to be associated with metachronous gastric cancer development [126], and in a DNA methylation analysis of anaplastic thyroid cancer (ATC), MAGI1 displayed promoter methylation as well as decreased expression in ATC compared with normal thyroid tissue [127]. Aberrant DNA methylation can result in both upregulation of oncogenes and the silencing of tumor suppressor genes [128].…”
Section: Regulation Of Magi1 Expressionmentioning
confidence: 99%